Analysis of Agribusiness Development Model in Kutalimbaru Regency: A Maqasid Syariah Perspective - Annisa Rizqiya; Muhammad Arif; Nurul Jannah (Islamiconomic : Jurnal Ekonomi Islam, 2025)
Agriculture plays a strategic role in providing food, bioenergy, and driving agro-industrial growth and commodity exports. However, the agricultural sector in Indonesia, including in Kutalimbaru District, Deli Serdang Regency, faces serious challenges, including declining interest among the younger generation and limited adoption of modern technology. Statistics Indonesia (BPS) data (2024) shows a decline of approximately 0.24 million casual workers in the agricultural sector nationally, which is also reflected in Kutalimbaru through reduced active land and a lack of farmer regeneration. This study aims to analyze the implementation of agricultural technology and understand the extent to which the principles of Maqasid Sharia can be integrated into local agribusiness practices. The research method used is a qualitative descriptive approach using observation techniques, in-depth interviews with local farmers, and documentation. The results indicate that limited access to information, minimal technology-based training such as smart farming and drip irrigation, and low institutional support are the main inhibiting factors. From a Maqasid Sharia perspective, strengthening the Kutalimbaru agricultural sector through agricultural technology supports the preservation of life (hifz al-nafs), protection of property (hifz al-mal), and environmental preservation (hifz al-bi'ah). The research conclusion emphasizes the importance of collaboration between the government, extension workers, and religious institutions in increasing agricultural technology literacy based on Islamic values to achieve productive, sustainable, and competitive agriculture.